Fungsi Komunikasi Antara Guru dan Siswa dalam Meningkatkan Kualitas Pendidikan (Studi Kasus Proses Belajar Mengajar pada SMP Negeri 3 Sindue) - Abdul Malik (Master of Communication Science Program, Universitas Diponegoro, 2015)
These results indicate that the Teaching and Learning in Secondary Schools 3 Sindue done by designing a program that includes curriculum consists of courses and programs outside the regular curriculum. Learning process between teachers and students will be increasingly weighted by itself when there is good communication between the two, in this case the knowledge transfer activities of the students. These activities will be implemented either through the implementation of discipline in the learning process by the method of extension of the theory in the room and on the practice field guide. The adopted method of learning is characterized by the intensity of face-to-face on a regular basis between teachers (educators) with students (the students) were conducted based scheduling subjects that have been made and determined before. Submission of teachers who use the language easily understood by learners, mejadikan the communication is effective.